Impacts of using PDCA in the requirements specification process - Costa, Alex Felipe Ferreira; Oliveira, Victória Tomé; Dantas, Valéria Lelli Leitão; Santos, Ismayle De Sousa; Andrade, Rossana Maria De Castro; Gomes, Rafael Lopes (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
The requirements specification plays a fundamental role in the software development process, impacting the final product’s quality directly. However, many projects have faced challenges related to the requirements specification. In this context, this article presents an experience report of implementing improvements in the requirements specification process of a software project in an academia-industry partnership. This report highlights the importance of enhancing that process to address issues associated with extensive and complex requirements documentation. Thus, we used the PDCA cycle (Plan-Do-Check-Act) and apply the lessons learned from the PDCA’s Check stage to improve the requirements specification process, making it clearer, more concise, and comprehensible for the stakeholders in the project. This article provides detailed descriptions of the PDCA cycle stages such as planning improvements, implementing actions and evaluation results and lessons learned. This PDCA-based approach showed to be effective in identifying and resolving problems in requirements specification activities, promoting positive changes in the requirements process.